Creating Community-University Partnerships in a Teacher Education Program: A Case Study - Woloshyn, Vera; Chalmers, Heather; Bosacki, Sandra (Alberta Journal of Educational Research, 2005)
In this study we explored a triad partnership among preservice department instructors and teacher candidates, community practitioners, and partners in a community-university research alliance (CURA). All partners were interviewed about their perceptions of their role in the partnership, the effectiveness of the collaboration, and the key lessons learned. Following content analyses of the conversations, three main themes emerged: the value of the partnership in this professional development project, required commitment and support, and challenges faced throughout the partnership. Recommendations for future partnerships in the educational context are discussed.